Depletion of androgen receptor low molecular weight isoform reduces bladder tumor cell viability and induces apoptosis. (28th April 2021) - Katleba, Kimberley; Lombard, Alan P.; Tsamouri, Maria-Malvina; Baek, Han Bit; Nishida, Kristine S.; Libertini, Stephen J.; Platero, Alexander J.; Ma, Ai-Hong; Pan, Chong-xian; Ghosh, Paramita M.; Mudryj, Maria
Abstract: Bladder cancer (BlCa) exhibits a gender disparity where men are three times more likely to develop the malignancy than women suggesting a role for the androgen receptor (AR). Here we report that BlCa cells express low molecular weight (LMW) AR isoforms that are missing the ligand binding domain (LBD). Isoform expression was detected in most BlCa cells, while a few express the full-length AR. Immunofluorescence studies detect AR in the nucleus and cytoplasm, and localization is cell dependent. Cells with nuclear AR expression exhibit reduced viability and increased apoptosis on total AR depletion. A novel AR-LMW variant, AR-v19, that is missing the LBD and contains 15 additional amino acids encoded by intron 3 sequences was detected in most BlCa malignancies. AR-v19 localizes to the nucleus and can transactivate AR-dependent transcription in a dose dependent manner. AR-v19 depletion impairs cell viability and promotes apoptosis in cells that express this variant. Thus, AR splice variant expression is common in BlCa and instrumental in ensuring cell survival. This suggests that targeting AR or AR downstream effectors may be a therapeutic strategy for the treatment of this malignancy. Highlights: First evidence that bladder tumors express androgen receptor low molecular weight isoforms splice variants. Depletion of all AR isoforms reduces cell viability and promotes apoptosis. A novel AR splice variant AR-v19 is present in most bladder tumor cells. Depletion of BlCa limits cell viability and induces apoptosis.